(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
A portion of operant literature supports significant production of knowledge about problem solving, observation response and contingency relations between responses with different probabilities of occurrence (Premack Principle). This study investigated possible convergences between a descriptive analysis of ordinal behavior and such portion of the operant literature. Conceptual and methodological analysis of publications have highlighted the relevance of the sequence of events functionally related to the characterization of the production of knowledge about problem solving, observation response and the Premack Principle enabling approaches between programs of research on complex behavioral repertoires as well as expansions in research strategies concerning ordinal responding